FUZZY ALGORITHM TO CONTROL REACTIVE POWER FLOW IN ELECTRIC NETWORK WITH NONLINEAR LOADS - H. B. Guliyev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
One of the important problems of efficient function of electric networks containing load nodes of nonlinear character of power consumption is reactive power compensation and maintaining voltage quality in a grid. The commonly used methods for compensation of harmonic currents by filtering devices make it possible to solve the problem in a narrow band of variation of current of a nonlinear load. In the reality stochastic character of power consumption of nonlinear load reveals itself in appropriate changes in harmonic components of voltage and their share in total load current. This could considerably change the magnitude and direction of reactive power flow in a grid and impair the existing processes of reactive power control. The scheme and the algorithm of control of capacitor banks in networks with non-linear load that are based on the use of fuzzy logic software are presented in the article. The results of model experiments analysis of the modes of the harmonic of the power flows on behalf of the 14-nodal scheme recommended by IEEE as well as the schemes of a real grid with powerful traction substation are presented. The mentioned results demonstrate that when harmonic components of voltages exceed normative magnitudes, the use of the proposed algorithm eliminates additional loading on the capacitor banks with higher harmonic currents whereas the control procedure acquires quality, the number of commutations is being reduced, the capacitor battery functions longer and the probability of its malfunction decreases.